Inventory of Medicinal Plants in Kampung Adat Urug, Urug Village, Sukajaya District, Bogor Regency - Muhammad Qais Izzuddin; Rodiyati Azrianingsih (Natural B, Journal of Health and Environmental Sciences, 2015)
This research purposed to find out species, preparation and uses of medicinal plants in Kampung Adat Urug. Ethnobotanical survey was conducted from November 2013 until May 2014 using interview (semi-structured) and observation activities. The respondents were determinated by snowball sampling with the head of Kampung Adat Urug as a key informant. The observation was conducted for documenting medicinal plants based on respondent recomendation. Data gained from this activity was qualitatively described. Medicinal plants used by the Kampung Urug were 53 species singly and 5 herbs. Those species belonged 27 families. The most recomended medicinal plants were Cardamom and Bitung Bamboo. Those plants often to treat cough with dringking extraxted water from trunk (dituak). Bitung Bamboo shoot soup is used to prevent aging. In Kampung Adat Urug, traditional midwife often use medicinal plants to make herbs for healing any diseases, such as headache, stomachache, kidney problem, and also increasing stamina for adult and women after pregnant. Medicinal plants and herbs which were recomended by respondents were adequate treatment for any diseases because they have evidences between ethic and emic